Calcineurin inhibitor-free immunosuppression in pediatric renal transplantation - Höcker, Britta; Tönshoff, Burkhard (Pediatric drugs, 2011)
The introduction, in the mid-1980s, of calcineurin inhibitors - namely ciclosporin (cyclosporine) and later tacrolimus - has significantly improved short-term renal graft survival by lowering acute rejection rates in both adult and pediatric kidney transplantation. Nonetheless, long-term transplant survival is still not satisfactory, with calcineurin inhibitor-induced chronic nephrotoxicity being one of the main causes of progressive nephron loss and declining renal transplant function. Hence, different immunosuppressant regimens have been proposed to avoid or ameliorate calcineurin inhibitor-induced nephrotoxicity. These comprise the use of non-depleting or depleting antibodies for calcineurin inhibitor minimization, calcineurin inhibitor avoidance, or calcineurin inhibitor withdrawal from mycophenolate mofetil-based immunosuppressant protocols. De novo use of a mammalian target of rapamycin (mTOR) inhibitor (sirolimus or everolimus) or conversion from a calcineurin inhibitor to an mTOR inhibitor may constitute another therapeutic option to avoid or reduce calcineurin inhibitor-induced nephrotoxicity.
Gesehen am 04.08.2022